Fashion consciousness: important role to plus-size women well-being - Büttner, Ana Julia (2022)
Objective: This research identifies how plus size women can find well-being through fashion consciousnessMethodology: We conducted sixteen semi-structured interviews with photography elicitation for content analysis.  All respondents were obese or overweight women following the Body Mass Index (BMI) criteria and selected through snowball sampling.Value: Fashion can help fat women find well-being, particularly fashion consciousness, which plays a vital role in fashion consumption. We demonstrated how fashion awareness could promote social inclusion and positive well-being to plus-size women even inside a symbolic violence context.  Results: There are two groups who follow the logic of commerce and the logic os arts: Fatshionists and women with fashion degrees. Virtual retail, together with fashion consciousness, enhance positive well-being. Specialised stores for plus-size women do not match their desire for self-expression, and this segregation causes negative well-being. Despite the Body Positive Movement, respondents still associated beauty with a regular body shape.  Theoretical contribution: We add fashion knowledge and consciousness to the three triggers presented by Scaraboto & Fischer (2013). Fashion consciousness enhances autonomy for plus size women promoting positive and negative well-being through fashion consumption even though these consumers are invisible to many fashion brands.Managerial contribution: Product development should consider the anthropometrics of plus-size women. Retail strategy should introduce plus size on physical stores to diminish the illegitimacy of these consumers and the symbolic violence.